Evaluation of dietary benfotiamine to enhance dietary carbohydrate utilization of njile tilapia (Oreochromis niloticus). - Lauzon, Quenstein Dizon
This dissertation investigated the effects of a high carbohydrate (HC) diet with or without benfotiamine supplementation in the Nile tilapia Oreochromis niloticus. Benfotiamine is a lipid soluble derivative of thiamine (Vitamin B1). The study aimed to evaluate the effects of HC and Hc supplemented with benfotiamine on (a) growth performance and efficiency, (b) attractability, ( c) glucose homeostasis; and (d) gene expression fo Nile tilapia (O. niloticus). For the feeding trial, a total of 180 larvae (ABW=0.01g) were randomly distributed into 9 tanks and fed on of the three experimental diets, namely, a low carbohydrate diet containing 15% carbohydrate; high carbohydrate diet (HC) containing 25% carbohydrate; and high carbohydrate diet (25%) supplemented with 0.02% benfotiamine (HCB) for 8 weeks. Increasing corn starch in the diet from 15% (i.e. control diet) to 25% (i.e.) HC diet did not have any effect on the growth performance nor feed efficiency of the NIle tilapia. In contrast, Nile tilapia fed with the HCB diet exhibited significantly attracted the most percentage of fish. For the sub-study on glucose utilization, two experiments were conducted to answer two questions: (1) Do the experimental diets, namely C, HC and HCB, elicit effects on the blood glucose levels in the Nile tilapia, and (2) Do the experimental diets affect glucose tolerance in the fish? For the first experiment, 63 Nile tilapia juveniles (ABW=5.3g) were randomly distributed into three tanks and fed either one of the three experimental diets for 48h. Blood was extracted periodically and blood sugar measured using a glucometer at time 0, 1h, 2h, 3h, 4h, 5h and 8h after feeding. For the glucose tolerance test, 63 Nile tilapia (ABW=11g) were fed the control diet for one week. Glucose was orally administered following an 18h fasting, after which blood was extracted periodically and blood glucose measured at time 0, 1h, 2h, 3h, 4h, 5h and 8h. Results revealed that dietary benfotiamine resulted in the post prandial reduction of blood sugar to the initial level (at 0h) after 5h for both experiments whereas the other groups fed the other diets did not return to the initial level and remained high at 5h. The HC group returned to the initial level at 8h. Lastly for the first study, Nile tilapia was subjected to the transcriptomic analysis to establish mechanism of such utilization. RNA was extracted from the whole body of Nile tilapia (ABW=0.07g) after 14-day feeding. By using RNA sequencing, a total of 222,492,264 clean reads were generated and were de novo assembled into 214,275 unigenes. Among the 361 differentially expressed genes (DEGs) in HCB vs HC, 207 DEGs exhibited significant upregulation while 154 DEGs significantly displayed downregulation. In this experiment, the most relevant findings were on the comparison between HCB and HC, since it has been shown above that the Nile tilapia was able to cope with the HC which was comparable with those fed the control diet (less carbohydrate diet). In the enrichment analysis, the highest number of pathways impacted by benfotiamine supplementation is under the main category Metabolism with 9 groups of pathways impacted, followed by the Genetic Information Processing and by Cellular processes, both had 4 groups of pathways. Under metabolism, the most impacted were lipid metabolism, glycan biosynthesis and metabolism and metabolism of cofactors and vitamins. Under genetic information and processing, the most impacted pathways were transcription, translation, folding, sorting and degradation and biosynthesis of secondary metabolites. Under Cellular processes, those with the highest hit were cell growth and death, transport and catabolism and cell motility. The second study aimed to determine the optimum level of dietary benfotiamine in the diet of the Nile tilapia (O. niloticus) fry. Five experimental diets were prepared, namely at 0.0% (control), 0.02%, 0.04%, 0.06% and 0.08% benfotiamine supplemented to 25% carbohydrate diet. A total of 525 Nile tilapia fry (ABW=0.07g) were randomly distributed in 15 tanks and fed with the experimental diets for 8 weeks. Nile tilapia fry fed the diet with 0.06% benfotiamine supplementation exhibited significantly the highest FABW, WG and SGR, but not statistically different with those fed with HCB incorporated with 0.02% benfotiamine. For this study, 0.02% benfotiamine supplementation was deemed optimum to enhance growth performance of Nile tilapia. The third study conducted to determine the optimum feeding rate for Nile tilapia fed with high carbohydrate (25% carbohydrate kg-1 diet) diet incorporated with the optimum level of benfotiamine (0.02%) in a controlled laboratory condition. Fish were fed diet with benfotiamine supplemented to 25% carbohydrate kg-1 diet at different satiation levels (100%, 90%, 80%, 70% and 60%). A total of 300 Nile tilapia fry (ABW=0.3g) were randomly distributed in 15 tanks fed with one of the five satiation levels for 8 weeks. Nile tilapia fed at 90% of satiation exhibited significantly the highest FABW, WG and SGR among other dietary treatments, and lowest FCR. This satiation level seemed ideal for Nile tilapia fry. Overall, these findings suggested that benfotiamine significantly enhanced the growth performance of Nile tilapia through increased weight gain, specific growth rate, feed intake and feed efficiency and down-regulated hyperglycemia. The data obtained here will be helpful in understanding beneficial effects of benfotiamine on the carbohydrate utilization specifically for Nile tilapia and is necessary for the development of cheaper formulated diets. Results obtained from transcriptomic analysis may help elucidate the underlying mechanisms behind the enhanced growth performance as well as carbohydrate utilization of O. niloticus. Furthermore, this study provides foundation for future genomic researches.